An Analysis on the Navy’s Defense Planning based on the potential phenomenon of Arms Races in Southeast Asia and the Minimum Essentials Force Strategy - Putra, Hendriman; Moeljadi, Moeljadi; Kusumaningrum, Adi (Technium Social Sciences Journal, 2021)
Indonesia as an archipelagic country which has thousand islands and an area of two-thirds of the total territorial waters as well as a strategic geographical location is very vulnerable to military and non-military threats. Thus, Indonesia should be providing an appropriate defense development methods to build its military strength, especially the Indonesian Navy, in order to make it capable to deal with the phenomenon of arms races in the Southeast Asia region and to protect Indonesian maritime jurisdiction from existing threats and conflicts. The research method used is descriptive with a qualitative approach. The results of this study are that arms races have become a phenomenon that can be destabilize the Southeast Asia security which is classified into several levels ranging from very low, low, moderate, high and very high, based on 8 (eight) factors as indicators of classification and definition. arms races; Minimum Essential Forces (MEF) is a national development mandate in the field of defense and security as well as a strategy used by the Government of Indonesia to enhance the capabilities and strength of the TNI, which is based on 3 (three) main components, such as capability based planning, threat based planning and flash points; and the Naval Concept of Operations (Conops) can be used as an additional component to harmonizes the 3 (three) main components that make up the MEF in order to create a professional and modern Navy with regional projection capabilities and global commitment.